Comparative Effectiveness of Antidiabetic Therapies on Clinical Outcomes in Type 2 Diabetes Mellitus Outpatients - Tandah, Muhamad Rinaldhi; Diana, Khusnul; Hidayat, Chairunisah; Ambianti, Nurul (Media Publikasi Cendekia Indonesia, 2025)
This study used observational analysis with retrospective data collection. A total of 303 outpatients with were included in this study. The research instrument used was secondary from medical record data and examination results of Fasting Plasma Glucose (FPG) and 2-hour plasma glucose (2-h PG) values when the patient first visited and the fourth month after the first visit. The patients' therapy is regarded as effective if the FPG test results range from 80-130 mg/dL and the 2-h PG test value is <180 mg/dL in the fourth month. In patients aged >60 years, it is said to be effective if the results of the FPG examination are around ≤ 180 mg/dL and the 2-h PG examination value is ≤200 mg/dL. Data were analyzed using Kruskal-Wallis analysis. Oral antidiabetics metformin and glimepiride had differences in observed effectiveness (p=0.000) < 0.05 for FPG and 2-h PG examinations in outpatients with type 2 diabetes mellitus. The type of oral antidiabetic glimepiride had differences in observed effectiveness (p=0.002) < 0.05 in the FPG examination and (p=0.006) < 0.05 in the 2-h PG examination. The oral antidiabetic drug groups metformin and glimepiride had differences in observed therapeutic effectiveness in outpatients with T2DM, while the insulin group and the combination group did not have differences in therapeutic effectiveness in T2DM patients.